Silver Clusters of Five Atoms as Highly Selective Antitumoral Agents Through Irreversible Oxidation of Thiols (Adv. Funct. Mater. 29/2022). (18th July 2022) - Porto, Vanesa; Buceta, David; Domínguez, Blanca; Carneiro, Carmen; Borrajo, Erea; Fraile, María; Davila‐Ferreira, Nerea; Arias, Iria R.; Blanco, José M.; Blanco, Maria C.; Devida, Juan M.; Giovanetti, Lisandro J.; et al.
Abstract : Antitumoral Agents In article number 2113028, M. Arturo López‐Quintela, Fernando Domínguez, and co‐workers report that Ag5 clusters show unique catalytic activities to oxidize thiols. They catalyze the complete oxidation of thiols present in cysteine, glutathione, and thioredoxin. This oxidation is tunable by relevant biological oxidants species (hydrogen peroxide and hydroxyl radical), allowing Ag5 to inhibit the thiol‐based antioxidants leading to the selective death of tumor proliferating cells.